Data Mining Approach in Retail Knowledge Discovery and Internet Technologies - Kaur, Simranjit; Baghla, Seema (Asian Journal of Engineering and Applied Technology, 2018)
Online shopping has a shopping channel or purchasing various items through online medium. Data mining is defined as a process used to extract usable data from a larger set of any raw data. The data set extraction from the demographic profiles and Questionnaire to investigate the gathered based by association. The method for shopping was totally changed with the happening to internet Technology. Association rule mining is one of the important problems of data mining has been used here. The goal of the association rule mining is to detect relationships or associations between specific values of categorical variables in large data sets.